Single dose pharmacokinetics of the novel transdermal donepezil patch in healthy volunteers - Kim YH; Choi HY; Lim HS; Lee SH; Jeon HS; Hong D; Kim SS; Choi YK; Bae KS (Dove Medical Press, 2015)
Yo Han Kim,1 Hee Youn Choi,1 Hyeong-Seok Lim,1 Shi Hyang Lee,1 Hae Sun Jeon,1 Donghyun Hong,2 Seong Su Kim,2 Young Kweon Choi,2 Kyun-Seop Bae1 1Department of Clinical Pharmacology and Therapeutics, College of Medicine, University of Ulsan, Asan Medical Center, Seoul, Republic of Korea; 2iCure Pharmaceutical lncorporated, Anseong, Gyeonggi-do, Republic of Korea Background: Donepezil is an acetylcholinesterase inhibitor indicated for Alzheimer’s disease. The aim of this randomized, single-blind, placebo-controlled, single-dose, dose-escalation study was to investigate the safety, tolerability, and pharmacokinetics of the donepezil patch in healthy male subjects. Methods: Each healthy male subject received a single transdermal donepezil patch (72 hours patch-on periods) of 43.75 mg/12.5 cm2, 87.5 mg/25 cm2, or 175 mg/50 cm2. Serial blood samples were collected up to 312 hours after patch application. The plasma concentrations of donepezil were determined by using a validated liquid chromatography–tandem mass spectrometry method. Pharmacokinetic parameters were obtained by noncompartmental analysis. Tolerability of the patches and performance of the patches (adhesion, skin irritation, residual donepezil content in the patch) were assessed throughout the study. Results: The study was completed by 36 healthy subjects. After patch application, the maximal plasma donepezil concentration (Cmax) and the area under the curve (AUC) increased in a dose-proportional manner. Median time to Cmax was ~74–76 hours (~2–4 hours after patch removal), and mean t1/2ß was ~63.77–93.07 hours. The average donepezil residue in the patch after 72 hours was ~73.9%–86.7% of the loading dose. There were neither serious adverse events nor adverse events that lead to discontinuation. Skin adhesion of the patch was good in 97.2% of the subjects. All skin irritations after patch removal were mild and were resolved during the study period. Conclusion: The donepezil patch appeared to be generally well tolerated and adhesive. Pharmacokinetic analysis of the donepezil patch demonstrated linear kinetics. Keywords: donepezil, transdermal patch, pharmacokinetics, healthy subjects